SOCIO-ECONOMIC PROFILE OF DAIRY FARMERS IN DIFFERENT PRODUCTION SYSTEMS OF TELANGANA - J. RAZIA SULTANA, M. RAJA SEKHAR, N. RAJANNA, M. MAHENDER, CH. SATYANARAYANA and (The Journal of Research, PJTSAU, 2019)
An investigation was carried out to study the socio-economic profile of dairy farmers of urban and peri urban production systems in and around Hyderabad city of Telangana. A total of 100 dairy farmers from both the production systems were selected by using simple random sampling technique for the study. A pre tested structured interview schedule was used to collect the data through personal interview. The information collected through interview schedule was analysed through suitable statistical tools. The findings of the socio-economic profile of the study revealed that majority of urban dairy farmers (82.0%) and peri urban dairy farmers (51.39%) lived in nuclear family and had medium annual income (84.0 and 60.0 %respectively), Most of the people participating in dairying belonged to backward community with an average age of 45.03 years. Majority had medium dairy farming experience. In urban areas majority of the dairy farmers were landless whereas in periurban areas majority were small farmers but dairying was the main occupation of farmers of both areas.There was a significant difference (P<0.01) between area under fodder crops, occupation and production systems.